A Design and Development of Wireless-Based Electric Load Control Monitoring System on Autobuses Vehicles - Mohammad Rizkyanto Rizky; Aad Hariyadi; Nugroho Suharto (Jurnal Jaringan Telekomunikasi, 2022)
The electrical installation structure on autobuses is generally still based on the old concept that relies on the fuse, where the fuse is the only safety as well as an indicator of the presence or absence of electrical power supply to several electrical devices contained in the autobus. For conditions where there is a short circuit on the line to the electrical load, the electrical equipment on the autobus cannot be operated again. With the problem in the electrical system on the autobus, a monitoring system for controlling the power used on the autobus vehicle was created automatically based on wireless. In this study, the system created using Arduino Uno is functioned as a server node. Then there is a sensor node which will later function to receive incoming data from the Ina219 sensor, then sent using wireless communication to the server node. Then on the server node, all data will be monitored via the LCD display and notification LED, then if there is excessive use the system will turn off the relay where the point is using excess power. From the test results, the sensor node is able to send data from the sensor node readings. Then it is sent to the Node Server and the results obtained are 2% for packet loss. The delay value is 0.29s for the highest result.